Molecular, morphological and agronomic characterization of the sweet potato (Ipomoea batatas L.) germplasm collection from Mozambique: Genotype selection for drought prone regions - Maquia, I.; Muocha, I.; Naico, A.; Martins, N.; Gouveia, M.; Andrade, I.; Goulao, L.F.; Ribeiro, A.I. (Elsevier, 2013)
Sweet potato (Ipomoea batatas (L.) Lam) is one of the most important root crops in Mozambique, ranking in the 3rd position, after cassava and maize. Within the scope of the national and regional strategies/initiatives, we have used a multi-analysis approach to characterize the national sweet potato germplasm collection at two different levels: i) genetic, morphological and agronomic diversity; and ii) agronomic potential (storage root yield, vine weight, biomass, harvest index and dry matter content) toward drought tolerance. This collection, composed by 44 accessions, comprises 28 genotypes cultivated in three different provinces of Mozambique (Gaza, Inhambane and Zambezia), nine from other African countries (Kenya, South Africa, Uganda and Zimbabwe), one from the United States of America, and six from CGIAR research centers (IITA and CIP). According to our results, the Mozambican germplasm bank presents a high level of diversity, comparable to those from the collections of the primary centers of origin and South Africa, therefore constituting of a good source of agronomic traits for breeding. Regarding drought tolerance, six Mozambican genotypes (Admarc, Chingova, Nhacoongo-1, Xihetamakote, Nwanatuyo, and Chissicuana-2), one from Uganda (NASPOT-5), one from Zimbabwe (Moz_white), one from Kenya (SPK 004), and one from the USA (Resisto) seem to have the highest potential to be used in regions with frequent drought seasons and in future breeding programs. The results showed that such integrated analysis can be used to successfully characterize the genetic material in terms of suitability to drought-prone regions, therefore helping sweet potato crop management, with economic and food security impacts.